Cardiovascular health in former elite male athletes - Johansson, J. K.; Kujala, U. M.; Sarna, S.; Karanko, H.; Puukka, P. J.; Jula, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2016)
To increase our knowledge on the effects of previous and current physical activity on cardiovascular health, we studied a group of Finnish male former elite athletes (endurance, n = 49; power, n = 50) and their 49 age and area-matched controls, aged 64-89 years. Body mass index (BMI), fasting serum glucose, lipids, blood pressure, and ultrasonography of cardiac and carotid artery structure and function were measured. Former endurance athletes smoked less, had lower prevalence of hypertension, and had higher intensity and volume of leisure time physical activity (LTPA) than the controls. No difference was detected in cardiac or carotid artery structure and function between these groups. Former athletes performing high-intensity LTPA were slightly younger (possible selection bias), had lower BMI and waist circumference, lower use of antihypertensives, lower prevalence of diabetes, lower pulse wave velocity, and higher carotid artery elasticity than former athletes not performing high-intensity LTPA. In conclusion, former athletes had a higher intensity and volume of LTPA than the controls. Athletes performing vigorous LTPA had more elastic arteries than athletes performing moderately or no LTPA. Vigorous LTPA through the whole lifetime associates with good cardiovascular health, although the previous medical history may play an important role